Predicting Destination Image in Creative Tourism: A Comparative between Tourists and Residents - David Dean; Dwi Suhartanto; Lusianus Kusdibyo (Politeknik Negeri Bandung, 2019)
This study’s objective is to examine tourist and resident experiences of creative tourist attractions through the development of an experience quality-destination model and assess the interrelationships among model factors: experience quality, perceived value, satisfaction, and destination image. The research was conducted across several creative tourism attractions in Bandung, Indonesia including cultural/traditional dancing, crafting, painting and games. Self-administered questionnaires were distributed to the visitors after they enjoyed the experience. Of the 421 questionnaires collected, 400 were useable for further analysis. The hypotheses are examined by using Partial Least Square (PLS). The proposed experience quality-destination model is a good fit for both the tourist and resident samples. For the tourist sample, all the direct effects among variables in the model are significant except for perceived value’s effect on destination image. For the resident sample, experience quality directly influences perceived value, and perceived value directly affects both satisfaction and destination image. The total effect of experience quality on destination image is significant for both samples.